Medical Encounters for Youth With Autism Spectrum Disorder: A Comprehensive Review of Environmental Considerations and Interventions. (April 2019) - Straus, Jolie; Coburn, Sarah; Maskell, Stephanie; Pappagianopoulos, Jessica; Cantrell, Kathryn
Approximately 1 in 59 youth are currently diagnosed with autism spectrum disorder (ASD), a neurodevelopmental disorder. In comparison to typically developing peers, youth with ASD encounter hospitalization at higher rates due to their heightened health care needs. While visiting the hospital is a stressor for youth with neurotypical needs, the experience contains unique challenges for those with ASD. This systematic literature review highlights research that considers the psychosocial impact of the hospital environment on the coping and adjustment of youth with ASD. Specifically, the review focuses on recommendations and interventions that may be used by health care professionals while supporting this population as they encounter the health care system. Ninety-six articles were identified as meeting inclusion and exclusion criteria. The findings suggest that practicing clinicians should implement a wide variety of interventions for youth with ASD including diversion techniques, comfort positions, and picture schedules. Although there are published evidence-based interventions for supporting youth with ASD in the hospital, most clinicians lack ASD-specific training. This article concludes with recommendations for future research.